The Role of Exosomes in Human Carcinogenesis and Cancer Therapy-Recent Findings from Molecular and Clinical Research - Stefańska, Katarzyna; Józkowiak, Małgorzata; Angelova Volponi, Ana; Shibli, Jamil Awad; Golkar-Narenji, Afsaneh; Antosik, Paweł; Bukowska, Dorota; Piotrowska-Kempisty, Hanna; Mozdziak, Paul; Dzięgiel, Piotr; Podhorska-Okołów, Marzenna; Zabel, Maciej; et al. (Cells, 2023)
Exosomes are biological nanoscale spherical lipid bilayer vesicles, 40-160 nm in diameter, produced by most mammalian cells in both physiological and pathological conditions. Exosomes are formed via the endosomal sorting complex required for transport (ESCRT). The primary function of exosomes is mediating cell-to-cell communication. In terms of cancer, exosomes play important roles as mediators of intercellular communication, leading to tumor progression. Moreover, they can serve as biomarkers for cancer detection and progression. Therefore, their utilization in cancer therapies has been suggested, either as drug delivery carriers or as a diagnostic tool. However, exosomes were also reported to be involved in cancer drug resistance via transferring information of drug resistance to sensitive cells. It is important to consider the current knowledge regarding the role of exosomes in cancer, drug resistance, cancer therapies, and their clinical application in cancer therapies.
Keywords: Exosomes; Neoplasms; Mammals; cancer; cancer therapies; exozómy; Drug Carriers; exosomes; savci; Carcinogenesis; Drug Delivery Systems; Animals; lidé; Humans; zvířata; karcinogeneze; nádory; drug resistance; nosiče léků; lékové transportní systémy